Economic freedom in the light of the Algerian Constitutions: a legal interpretation - lakehal, saleh (The journal of Teacher Researcher of Legal and political Studies, 2025)
After independence, Algeria adopted a socialist model in which the state owned the main means of production. Faced with the limitations of this system, the public authorities embarked on reforms that gradually paved the way for a market economy, marked by implicit recognition of economic freedom in the 1989 Constitution, followed by explicit affirmation of this principle in 1996